Osváth Viktor egyházi énekfeldolgozásai - PÉTER, Éva (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Church choir works by Viktor Osváth. The aim of this paper is to present the choral pieces composed by Viktor Osváth, who was a pastor and church musician. The compositions had at their basis tunes of psalms and tunes of praise from the official hymn book of the Hungarian Reformed Church. These choral pieces can be found in the three volumes with the title Meghódol lelkem tenéked, nagy Felség (My soul is worshiping You, great Majesty). The volumes contain 105 pieces. Following practical considerations, the three volumes presents the choral pieces at different difficulty levels and in different groups according to genre: choral pieces for single gender choir, choral pieces for mixed choir and choral pieces with instrumental accompaniment.